2021
DOI: 10.3390/ijms22168515
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Proteomic Analysis of Selenoprotein T Knockout Mice by TMT: Implications for the Role of Selenoprotein T in Glucose and Lipid Metabolism

Abstract: Selenoprotein T (SELENOT, SelT), a thioredoxin-like enzyme, exerts an essential oxidoreductase activity in the endoplasmic reticulum. However, its precise function remains unknown. To gain more understanding of SELENOT function, a conventional global Selenot knockout (KO) mouse model was constructed for the first time using the CRISPR/Cas9 technique. Deletion of SELENOT caused male sterility, reduced size/body weight, lower fed and/or fasting blood glucose levels and lower fasting serum insulin levels, and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Being a major protein disulfide reductase in the cell, TXNRD1 is involved in the control of antioxidant defense [ 53 ]. Moreover, SELENOT, also an ER-resident selenoprotein, has been reported to be involved in the regulation of glucose metabolism [ 54 , 55 ]. However, we found that the expression levels of TXNRD1 and SELENOT did not change in the livers of KO mice at all ages ( Figure S2 ), suggesting that SELENOF KO had no significant effect on their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Being a major protein disulfide reductase in the cell, TXNRD1 is involved in the control of antioxidant defense [ 53 ]. Moreover, SELENOT, also an ER-resident selenoprotein, has been reported to be involved in the regulation of glucose metabolism [ 54 , 55 ]. However, we found that the expression levels of TXNRD1 and SELENOT did not change in the livers of KO mice at all ages ( Figure S2 ), suggesting that SELENOF KO had no significant effect on their expression.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that LIRA can reverse the expression of SelT in the model group, which may be related to oxidative stress, etc ( 25 ). TXNIP, which is involved in the activation of the NLRP3 inflammasome, is closely related to the onset of type 2 diabetes mellitus ( 26 ). As claimed by Bai S et al, MMP-2 is related to the progression of chronic diabetes complications, and exosomal circ_DLGAP4 regulates the expression of miR-143 and targets the ERBB3/NF-κB/MMP-2 axis, which triggers the occurrence of diabetic nephropathy ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Then, 100 μg of each peptide mixture sampled was labeled, using tandem mass tag (TMT)-6plex reagent (Thermo Fisher Scientific, 90,064CH, USA), according to the manufacturer's instructions. 20 In brief, 200 μg of digested proteins were mixed with 30 μL standard buffer (4% SDS, 100 mM DTT, 150 mM Tris-HCI, pH 8.0). The detergent, DTT and other low molecular weight components were then removed by repeated ultrafiltration (MicroCon units, 10 kDa) in uric acid buffer (8 M urea, 150 mM Tris-HCl pH 8.0).…”
Section: Proteolysismentioning
confidence: 99%